Lectotypifications in Brazilian Porophyllum (Asteraceae: Tageteae) - Carneiro, Camila Rezendo; Ritter, Mara Rejane (Phytotaxa, 2016)
Porophyllum Guettard (1754: 377) is a genus of the tribe Tageteae Cassini (1819: 162), which contains 28 species occurring from southwestern USA to northern Argentina (Johnson 1969).